2021
DOI: 10.1149/1945-7111/abda03
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange Conduction of Lithium Ion in a Pentaglyme-Lithium Bis(trifluoromethylsulfonyl)amide Super-Concentrated Electrolyte

Abstract: Ligand exchange conduction or hopping conduction which means ions move faster than their ligands or solvents, is one of the striking phenomena in electrochemistry. Here, we report a glyme-based electrolyte where ligand exchange conduction takes place. The electrolyte is a concentrated pentaglyme (G5) solution of lithium bis(trifluoromethylsulfonyl)amide (LiTf2N; Tf = SO2CF3) with molar ratio of [G5]/[LiTf2N] = 1/2. Since a diglyme (G2) solution [G2]/[LiTf2N] = 1/1 which has the same molar ratio of ether oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…In traditional liquid electrolytes, solvation shell molecules are in rapid dynamic exchange with free solvent molecules. This rapid ligand exchange implies that a Li + can diffuse between different locations simply by exchanging its solvating molecules. Such a ligand exchange/hopping mechanism exists in a range of highly concentrated liquid electrolytes. However, a high salt concentration in these electrolytes introduces intense ion–ion interactions, which generally reduce conductivity. Moreover, the conductivity of “polymer-in-salt” electrolytes, the polymerized version of highly concentrated liquid electrolytes, is still not suitable for commercial applications, even after several decades of research. , …”
Section: Ion and Solvent Diffusion And Conductivitymentioning
confidence: 99%
“…In traditional liquid electrolytes, solvation shell molecules are in rapid dynamic exchange with free solvent molecules. This rapid ligand exchange implies that a Li + can diffuse between different locations simply by exchanging its solvating molecules. Such a ligand exchange/hopping mechanism exists in a range of highly concentrated liquid electrolytes. However, a high salt concentration in these electrolytes introduces intense ion–ion interactions, which generally reduce conductivity. Moreover, the conductivity of “polymer-in-salt” electrolytes, the polymerized version of highly concentrated liquid electrolytes, is still not suitable for commercial applications, even after several decades of research. , …”
Section: Ion and Solvent Diffusion And Conductivitymentioning
confidence: 99%
“…Recently, Murase et al found that Li + diffuses fastest in LiTFSA-rich pentaglyme (G5) mixtures. [29] In systems where Li + hopping is suggested, the Li + transference number is important. Hittorf's response and traditional methods of electromotive force, [30] electromotive force and constant current or constant potential polarization, and NMR methods have been compared for representative electrolytes used in lithium-ion secondary batteries.…”
Section: Final Remarkmentioning
confidence: 99%
“…28−30 Glymes-based electrolytes have many important features such as high ionic conductivity (∼10 −3 S cm −1 at ambient temperature), wide range of electrochemical stability window (>4 V), less volatility, and the least flammability and toxicity. 31,32 In addition, such electrolytes show chemical stability along with thermal stability over a wider range of temperatures. The glyme-based electrolytes exhibit much better discharge kinetics and has the ability to retain higher capacity when used in batteries as compared to the other carbonate-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…via the ether oxygen present in different glymes in a ratio of 1:( n + 1). Such coordination occurs in each molecule by donating its electron density through the lone pair of electrons of the oxygen. Various studies are reported on the mixture of different salts and glymes, referred to as “solvate ionic liquids (SILs)”, employed as electrolytes in different reported rechargeable batteries. Glymes-based electrolytes have many important features such as high ionic conductivity (∼10 –3 S cm –1 at ambient temperature), wide range of electrochemical stability window (>4 V), less volatility, and the least flammability and toxicity. , In addition, such electrolytes show chemical stability along with thermal stability over a wider range of temperatures. The glyme-based electrolytes exhibit much better discharge kinetics and has the ability to retain higher capacity when used in batteries as compared to the other carbonate-based electrolytes .…”
Section: Introductionmentioning
confidence: 99%